An ecological and embodied approach for training the racecar driver - Ziv, Gal (Frontiers in Sports and Active Living, 2024)
In the dynamic sport of racecar driving, split-second decisions and rapid execution are imperative. Such an environment requires a tight functional coupling of perception and action. This paper introduces an approach for training racecar drivers rooted in ecological and embodied perspectives. It delves into three pivotal affordances of racecar driving: turn-ability, overtake-ability, and defend-ability. The paper also discusses the relevant environment and equipment (i.e., simulators) that can be useful for training racecar drivers. In addition, practice activities relevant for the actual racetrack or to the simulator are discussed. Coaches are encouraged to try and implement the proposed training strategies (or parts of it), evaluating their impact on racing performance. Furthermore, researchers can continue exploring these principles, fostering a fusion of empirical insights with practical expertise from coaches and racing communities. By synergizing empirical research with insights from practitioners, we can refine the strategies employed in the training of racecar drivers.